Pulmonary hypertension complicating multiple myeloma - Krishnan, Udhay (Pulm Circ, 2015)
Abstract. Pulmonary hypertension (PH) is an infrequently reported complication of multiple myeloma (MM). PH has been more commonly associated with amyloidosis, myeloproliferative diseases, and the POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, skin changes) syndrome. PH in MM is typically mild to moderate and may be secondary to a variety of conditions, which include left ventricular dysfunction, high-output cardiac failure, chronic kidney disease, treatment-related toxicities, and precapillary involvement. We describe 3 patients with MM and severe PH. Each patient underwent right heart catheterization. All patients demonstrated elevated pulmonary pressures, transpulmonary gradients, and pulmonary vascular resistance. Each patient was ultimately treated with pulmonary vasodilator therapy with improvement in cardiopulmonary symptoms. Additional studies are needed to define the prevalence, prognosis, and pathogenesis of PH in this complex population and to help clarify who may benefit from targeted PH therapy.